PELAKSANAAN PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA KRISTEN KELAS IV SDN BARATAJAYA SURABAYA - Yusak Yusak (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2020)
Abstract: This research was motivated by the low learning outcomes of Christian Religious Education with a grade average of 61. Meanwhile, the minimum completeness criteria for Christian Religious Education were 75. Among the 9 students, only 3 students achieved minimum completeness criteria with 44% classical completeness.  This research is a classroom action research which aims to improve the learning outcomes of the fourth grade students of SDN Baratajaya Surabaya by applying the Two Stay-Two Stray Technique Cooperative model.  Data collection instruments in this thesis are teacher and student activity sheets and learning outcomes.  This study presents the learning outcomes obtained by an average learning outcome before action 61 increases to 66 in cycle I. In cycle II increases to an average of 82. Teacher activity in the first cycle of the first meeting the percentage obtained is 2.85 with a percentage of 66% including in the good category, in the second cycle was 3.33 in the very good category with a percentage of 88%.  This shows that there is an increase in teacher skills by 0.48 with a percentage of 48%.  While the average student activity in the first cycle was 3.09 with a percentage of 66%, in the second cycle it was 3.17 with a percentage of 88% so there was a fairly good increase, namely 0.08 with a percentage of 8%.  This shows that an increase in teacher skills and student activity affects the increase in student learning outcomes so that the quality of Christian Religious Education learning increases. Keywords : Two Stay-Two Stray Cooperative Techniques, Learning Outcomes of Christian Religious Education